Meningkatkan Kemandirian Petani melalui Pengembangan Kelembagaan Petani di Kecamatan Polokarto - Sapja Anantanyu; Dwiningtyas Padmaningrum; Sutarto Sutarto (Universitas Sebelas Maret, 2004)
In developing countries, however, the farmer organizations are still weak in one side and there are a variety of constraints in development of such organizations in other side. Similar experience occurs with farmer organizations in District of Sukoharjo. With this context, it is necessary for the agricultural service to carry out an action plan to promote farmer organizations in order to enhance self reliance of the organizations. A conceptual framework should be formulated based on the following considerations: (a) continue the existing program of farmer organizations developed and its improvement in the future; (b) analyze the strengths and weakness of the existing farmer organizations; (c) establish the ideal conditions of the farmer organizations, especially in term of self reliance.This studi formulates an alternaiveframework for intervention which cover the followings: (a) increase the capacity of extension agents, especially in delivering guidance and technical assistant; (b) increase the capacity of farmer organizations to formulate participatory plan; (c) enhance the role of extension agents, especially in facilitating the activities of farmer organizations.Improvement of the capacity of farmer organizations can be done through increasing motivation (AMT), master of technique of productive activities and it is important to assist the organizations for their marketing products. Motivation and stimulation services shoul be directed to self reliance process of the farmer organizations and the members.